ANALYSIS OF FINANCIAL DISTRESS IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) IN THE PERIOD OF 2013-2014 USING DISCRIMINANT ANALYSIS - Limbong, Rizkie Imadudien (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study tries to determine the indication of financial distress using the Altman Z-score analysis manufacturing companies are listed on Indonesian Stock Exchange during 2013-2014. Analysis Altman Z-Score uses five financial ratios. Which are Working Capital To Total Assets , Ratio of Retained Earnings Against Total Assets / Retained Earnings to Total Assets , Ratio of EBIT Against Total Assets / Earnings before Interest and Taxes to Total Assets, Equity Capital ratios Market Value Book Value Against Debt / Market Value of Equity to Book Value of Total Debts, and Sales ratio to Total Assets / Sales to Total Assets. This quantitative descriptive research examine the financial statements of companies manufacturing and conducts critical studies using discriminant analysis of Altman Z-Score, which a new function discriminant. The nature of the research is a replication of previous studies. This study uses a sample of 65 manufacturing companies through purposive sampling technique. The results of the Altman Z-Score analysis have shown of the five variables. Being used variable Capital Ratio Working Against Total Assets, ratio of Retained Earnings to Total Assets, ratio of EBIT Against Total Assets / Earnings before Interest and Taxes to Total Assets, variable ratio of Market Value Share Capital to Book Value Debt / Market Value of Equity to Book Value of Total Debts, and variable Sales ratio to Total Assets / Sales to Total Assets, only variable turnover ratio Total Assets / Sales to Total Assets is the most influential variable significant to find indications of group of companies experiencing financial distress. Keywords: financial distress, discriminant analysis, Altman Z-Score method, manufacturing companies